A study of Nigeria's informal sector volume 1: statistics on Nigeria's Informal Sector - Central Bank of Nigeria; Federal Office of Statistics; Nigerian Institute of Social and Economic Research (Nigeria: Central Bank of Nigeria, 2001)
In-depth study on the size and structure of the Nigerian informal sector. The study reveals that the contribution of the informal manufacturing sector to the GDP was only 4.7 percent in 1998. In addition the share of the manufacturing sector as a whole in the GDP was 7.0 percent, and the contribution of the entire informal sector (agricultural sector inclusive) to GDP was only 37.8 percent.
rpm 08/06/2018
Loans
Keywords: Manufacturing; Nigeria